Investigation of outdoor BTEX: Concentration, variations, sources, spatial distribution, and risk assessment. (November 2016) - Miri, Mohammad; Rostami Aghdam Shendi, Maryam; Ghaffari, Hamid Reza; Ebrahimi Aval, Hamideh; Ahmadi, Ehsan; Taban, Ebrahim; Gholizadeh, Abdolmajid; Yazdani Aval, Mohsen; Mohammadi, Amir; Azari, Ali
Abstract: The aim of this study was to measure BTEX (benzene, toluene, ethylbenzene, and xylenes) concentrations in the ambient air of Tehran, the capital of Iran, and investigate their seasonal variations, probable sources, spatial mapping, and risk assessment. The concentrations of BTEX were measured using a continuous monitoring device installed in seven stations around the city. Spatial mapping procedure was conducted using the inverse distance weighting (IDW) method. Monte Carlo simulation was used to assess the carcinogenic and noncarcinogenic risks imposed by BTEX. The highest and lowest annual mean concentrations of toluene and ethylbenzene were recorded as 16.25 and 3.63 μg m −3, respectively. The maximum (6.434) and minimum (3.209) toluene/benzene (T/B) ratio was observed in summer and winter, respectively. The spatial distribution of BTEX pollution indicated that the highest concentrations were found along the major roads because of heavy traffic. Spearman's rank correlation coefficients and concentration ratios showed that BTEX were produced by the multiemission sources. The mean of inhalation lifetime cancer risk (LTCR) for benzene was 3.93 × 10 −7, which is lower than the limits recommended by the United States Environmental Protection Agency (US EPA) and the World Health Organization (WHO). The hazard quotient (HQ), noncarcinogenic risk index, for all BTEX compounds was <1. The obtained results showed no threat of BTEX concentrations to human health. However, as the concentrations of BTEX will increase due to the rapid growth of vehicles and industrial activities, much effort is required to control and manage the levels of these compounds in the future. Highlights: Seasonal variation, spatial mapping, photochemical aging, and risk assessment of BTEX in the ambient air of Tehran were investigated. . The maximum and minimum concentrations of BTEX were observed for toluene and ethylbenzene, respectively. Spatial distribution of BTEX pollution showed that the highest concentrations were found along the major roads because of heavy traffic. The cancer risk of benzene and noncarcinogenic risk of BTEX were in the acceptable range.